Self-Assessment Tools and Participatory Techniques. A Zoom on the Dyad “Rubrics” and “Online Focus Groups” - Capozza, Viviana; Lo Presti, Veronica; Martire, Fabrizio (Italian Sociological Review, 2024)
In the methodologies for evaluation the use of rubrics as a specific tool for competences assessment (Cortoni & Lo Presti, 2018) is supported by a wide research tradition, especially in the pedagogical field, that has circumscribed their application within dynamic learning contexts (Davidson, 2005). In didactic-educational environments, the administration of self-assessment rubrics can accompany and assist the learning process of students, stimulating in them the acquisition of critical self-reflection skills and drawing attention to those fields of experience that are traditionally connected to the teacher’s evaluative sphere (performance assessment, learning tasks, innovative teaching processes, etc.) (Dawson, 2015). In the research The Social Impact Assessment of DaD after COVID-19, promoted and funded by Sapienza University of Rome, combining tools for competences self-assessment (rubrics) and participatory research techniques (focus groups) has been particularly fruitful since it has helped students discuss the main changes experienced because of the pandemic regarding: i. learning styles; ii. leisure activities; iii. relationships with classmates and teachers. Combined with online participatory techniques, rubrics have maintained their nature as a non-reactive tool (Ametrano et al., 2001). In particular, the dialogic dimension generated by the focus group has made possible to neutralize the distorting effects associated with the concept of performance, preventing respondents from providing answers conditioned by social desirability. This has made possible to focus the discussion on specific aspects of the individual’s experience, making the scoring process more closely aligned with the lived experience.